A novel variant leads to WT1-related nephrotic syndrome and differences of sex development: a case report - Gao, Shan; Wang, Dahai; Ding, Xingmei; Bai, Cui; Nie, Nana; Chang, Hong; Zhang, Ranran; Liu, Jia; Zhang, Qiuye; Liu, Lin; Lin, Yi (Frontiers in Pediatrics, 2025)
BackgroundThe Wilms Tumour gene 1 (WT1, NM_024426.6) holds significant importance in the developmental processes of the kidneys and gonads. Herein, we report a case of nephrotic syndrome and differences of sex development in a patient with novel mutations in WT1 gene.MethodsThe child, identified as female based on social gender, exhibited symptoms at 6 years of age and was diagnosed with steroid-resistant nephrotic syndrome (SRNS). Renal biopsy findings indicated focal segmental glomerulosclerosis. Whole-exome sequencing unveiled a novel variant, c.1447 + 6(IVS9)T > C, in the WT1 gene, and karyotypic analysis revealed 46, XY, aligning with the phenotypic presentation of Frasier syndrome (FS, OMIM#136680) associated with WT1 gene mutation. The influence of gene variants on mRNA splicing was examined using in vitro minigene assays.ResultsThe variant was classified as likely pathogenic (PS2 + PM2_Supporting + PP3) in accordance with American College of Medical Genetics and Genomics (ACMG) guidelines. in vitro minigene experiments demonstrated that the c.1447 + 6(IVS9)T > C variant altered the splicing pattern of exon 9 in the WT1 gene from two isoforms to a single form, thereby supporting its pathogenicity.ConclusionThrough high-throughput sequencing and in vitro minigene splicing experiments, the c.1447 + 6T > C variant in the WT1 gene was supported as the underlying genetic cause in the child patient, thereby expanding the spectrum of gene variants of WT1 gene and enhancing our comprehension of the molecular pathogenesis of this disorder.